2020
DOI: 10.1002/cncy.22381
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cytology smears improves success rates of RNA‐based next‐generation sequencing gene fusion assays for clinically relevant predictive biomarkers

Abstract: Background The use of RNA‐based next‐generation sequencing (NGS) assays to detect gene fusions for targeted therapy has rapidly become an essential component of comprehensive molecular profiling. For cytology specimens, the cell block (CB) is most commonly used for fusion testing; however, insufficient cellularity and/or suboptimal RNA quality are often limiting factors. In the current study, the authors evaluated the factors affecting RNA fusion testing in cytology and the added value of smears in cases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…At our institution, molecular testing, including high‐throughput assays such as next‐generation sequencing, have been validated on cytology smears, cytospin preparations, and cell block preparations. Prior studies from our group have demonstrated that including cytology smears in our molecular assays has significantly improved the number of specimens that are adequate for testing 39,43 . This is in keeping with the increased number of molecular test requests over the past decade as seen in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At our institution, molecular testing, including high‐throughput assays such as next‐generation sequencing, have been validated on cytology smears, cytospin preparations, and cell block preparations. Prior studies from our group have demonstrated that including cytology smears in our molecular assays has significantly improved the number of specimens that are adequate for testing 39,43 . This is in keeping with the increased number of molecular test requests over the past decade as seen in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Multiple targeted therapeutic agents have been approved by the FDA for various malignancies, and identification of these molecular targets from clinical samples is absolutely essential 37 . Molecular studies have traditionally been performed on histological blocks; however, several studies have demonstrated that cytological specimens provide excellent substrates for molecular analysis and can provide clinically relevant genomic information that helps guide patient management 38‐40 …”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing is not affected by intronic regions but RNA extraction is more complicated than DNA, especially purification from FFPE specimens, as it can be highly degraded with the possibility to invalidate the run (50). However, in this setting, cytological samples as direct smears instead of CB preparation improve the adequacy of cytological material for RNA fusion testing for predictive biomarkers, as reported (51).…”
Section: Massive Parallel Sequencingmentioning
confidence: 97%
“…At the moment, most of the major studies use tissue samples for NTRK status assessment [109][110][111]. However, detection can be possible with cytological samples and even liquid biopsies [109,[112][113][114][115]. Several techniques of detection have been developed, including immunohistochemistry (IHC), molecular biology approaches (NGS and RT-PCR), and multiplex digital colorcoded barcode technology on tissue sections .…”
Section: Brafmentioning
confidence: 99%
“…Depending on the quality and quantity of the nucleic acids extracted from the sample, false negative results can be obtained [78,81,109,119,121]. Depending on the case, these approaches could be performed with cytological samples, but only a few studies in this area have been performed to date and studies comparing cytological and tissue samples are strongly needed [109,[112][113][114][115]. The detection of NTRK fusions can also be envisaged with a liquid biopsy, but the sensitivity of such an approach is still unknown and needs to be determined.…”
Section: Brafmentioning
confidence: 99%